Uruguayan Surgery in Pugnalin's time - Praderi, Raúl (Cirugía del Uruguay, 1980)
The author reports the initial' period of uruguayan abdominal surgery that began with oophorectomies performed by Estrázulas in 1874 and succesfully by Spada and Pugnalin in 1875. Dr. Pugnalin's figure brighted around fue eid a!: the century, he graduated in Bologna and. beea.-e c-man of Clinical Surgery from 1879 to 399, = Dean o!' our Faculty. He first introduced ·e,.s cd lir.erian surgery and la ter aseptic. 'gecy. The first cases of gastric and uterine surgery in Uruguay besides sone biographics data about surgeons who acted in that time are transcript and commented.